Iowa Birdline update, January 4-5, 1993 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1993)
Email for the Iowa Birdline update for January 4-5,1993. Highlights of the update include sightings of a Short-eared Owl, a male Rose-breasted Grosbeak, a female Mountain Bluebird, a Snowy Owl and a first year Iceland Gull. Also included are handwritten notes for the next week's update with sightings of a first year Glaucous Gull, Red-breasted Nuthatch and Golden-crowned Kinglets. Epson - sheet feed/flatbed